Role of Prenatal Hypoxia in Brain Development, Cognitive Functions, and Neurodegeneration - Nalivaeva, Natalia N.; Turner, Anthony J.; Zhuravin, Igor A. (Frontiers in Neuroscience, 2018)
This review focuses on the role of prenatal hypoxia in the development of brain functions in the postnatal period and subsequent increased risk of neurodegenerative disorders in later life. Accumulating evidence suggests that prenatal hypoxia in critical periods of brain formation results in significant changes in development of cognitive functions at various stages of postnatal life which correlate with morphological changes in brain structures involved in learning and memory. Prenatal hypoxia also leads to a decrease in brain adaptive potential and plasticity due to the disturbance in the process of formation of new contacts between cells and propagation of neuronal stimuli, especially in the cortex and hippocampus. On the other hand, prenatal hypoxia has a significant impact on expression and processing of a variety of genes involved in normal brain function and their epigenetic regulation. This results in changes in the patterns of mRNA and protein expression and their post-translational modifications, including protein misfolding and clearance. Among proteins affected by prenatal hypoxia are a key enzyme of the cholinergic system-acetylcholinesterase, and the amyloid precursor protein (APP), both of which have important roles in brain function. Disruption of their expression and metabolism caused by prenatal hypoxia can also result, apart from early cognitive dysfunctions, in development of neurodegeneration in later life. Another group of enzymes affected by prenatal hypoxia are peptidases involved in catabolism of neuropeptides, including amyloid-β peptide (Aβ). The decrease in the activity of neprilysin and other amyloid-degrading enzymes observed after prenatal hypoxia could result over the years in an Aβ clearance deficit and accumulation of its toxic species which cause neuronal cell death and development of neurodegeneration. Applying various approaches to restore expression of neuronal genes disrupted by prenatal hypoxia during postnatal development opens an avenue for therapeutic compensation of cognitive dysfunctions and prevention of Aβ accumulation in the aging brain and the model of prenatal hypoxia in rodents can be used as a reliable tool for assessment of their efficacy.